2019
DOI: 10.1002/star.201800314
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and In Vitro Starch Digestibility of Noodles Substituted with Tartary Buckwheat Flour

Abstract: The effects of Tartary buckwheat flour (TBF)/wheat flour ratio on the physical properties, and starch digestion, of noodles are investigated. Incorporation of TBF significantly changes the physical character of noodles. As TBF levels increase in noodles, the color of dough sheet become darker and noodle texture is affected deleteriously. Starch gelatinization temperature increases with TBF inclusion, and the relaxation time by low‐field nuclear magnetic resonance (LF‐NMR) system (including T21, T22, and T23) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
(65 reference statements)
0
10
0
1
Order By: Relevance
“…The area under the curve (AUC) was calculated according to Jia et al . (2019) to depict the amount of reducing sugar released when foods are consumed after 2 h (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area under the curve (AUC) was calculated according to Jia et al . (2019) to depict the amount of reducing sugar released when foods are consumed after 2 h (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro enzymatic starch digestion was used to imitate the digesting process of tested samples in the stomach and small intestine. The area under the curve (AUC) was calculated according to Jia et al (2019) to depict the amount of reducing sugar released when foods are consumed after 2 h (Fig. 1).…”
Section: Starch Digestibility and Predicted Glycaemic Responsementioning
confidence: 99%
“…Several approaches have been taken to reduce the glycemic response of noodles. It is found that noodles made from Tartary buckwheat flour could reduce the release of reducing sugar with an in vitro starch digestion and the 45% addition of Tartary buckwheat in noodles could benefit human health [17]. Apart from the starch, other ingredients in noodles, such as protein content [9] or the binding agent [18], can also affect noodle digestion.…”
Section: Introductionmentioning
confidence: 99%
“…The eGI values of GBN decreased gradually with the increase of GBP addition. This was probably due to the low concentration of starch and the higher content of fibril in GBP than in the wheat flour, which decreased the starch digestibility and the eGI values of noodles [ 52 ]. Similar changes were observed by Meixia Fu and co-workers [ 53 ], when buckwheat was mixed with wheat flour and made into noodles.…”
Section: Resultsmentioning
confidence: 99%